Trends in tuberculosis mortality among older adults in China, 2004–2021: a Joinpoint regression and age–period–cohort analysis - Zhang, Mengdi; Wang, Xin; Xiao, Yiran; Wang, Qiqi; Huang, Fei; Ren, Xiang; Guo, Xiaomin; Sun, Wenshan; Deng, Jinqi; Jiang, Qi; Liu, Jianjun; Zheng, Wenjing; et al. (Frontiers in Public Health, 2025)
BackgroundTuberculosis (TB) remains a major public health problem in China and globally, particularly among older adults. This study aimed to examine secular trends in TB mortality among older adults in China and the net effects of age, period, and cohort.MethodsData from the National Disease Surveillance Points (DSPs) system were analyzed using Joinpoint regression to determine annual changes in TB mortality among individuals aged 60 years and older from 2004 to 2021. An age–period–cohort (APC) analysis using the intrinsic estimator (IE) method was conducted to estimate the independent effects of age, period, and cohort.ResultsThe age-standardized TB mortality rate was 5.68 per 100,000, with higher rates observed in men, rural areas, and western regions. TB mortality among older adults declined overall from 2004 to 2021, although the rate of decline has slowed in recent years. The APC analysis revealed increased TB mortality with age, with the relative risk (RR) rising from 0.57 in the 60–64 age group to 1.53 in the 80–84 age group. The period effect decreased from 2007 to 2021, showing a higher risk effect in rural areas (RR = 1.51) than in urban areas (RR = 1.16) during 2007–2011, but this trend reversed in the period 2017–2021. The cohort effect generally declined, with the exception of certain demographic groups that showed an increase in the 1952–1956 and 1957–1961 birth cohorts.ConclusionTB mortality among older adults in China decreased from 2004 to 2021, although the decline has slowed in recent years. Variations in age, period, and cohort effects highlight differences by gender, urban and rural areas, and regions, providing insights for targeted intervention strategies.